Environmental Education: To develop sustainability competencies related to experimentation with environmental materials among secondary school students - Shahat, Hussein Ahmed; Al-Ruwaili, Hamdah Ayed Sayah; Aljaafari, Marram zakariaa (International Journal of Innovative Research and Scientific Studies, 2025)
The study aims to measure the impact of environmental education on the development of sustainability competencies (SC) related to experimentation with environmental materials among secondary school students. Therefore, the quasi-experimental approach was used. The study sample consisted of 80 female students enrolled in the second year of secondary school, general track 2024-2025, in private education schools in Al-Ahsa. They were selected using a simple random method. They were divided into two equal groups: one experimental group (40 students) and one control group (40 students). The instruments included the Sustainability Competencies Scale Related to Experimentation in Materials (SCEEM) and the training program represented. The results showed that there was a statistically significant difference between the average scores of the experimental and control groups in the post-measurement on the SCEEM scale, in favor of the experimental group. There were no statistically significant differences between the average scores of the experimental group in the post-measurement and follow-up on the SCEEM scale, as the total value of the test reached 1.610, which is an insignificant value, indicating the continuity of the program’s effect and its effectiveness. The study emphasizes the need for future research on sustainability competencies and environmental education, especially in material experimentation. It suggests exploring the link between these competencies and practical practices, individual differences, and academic performance. Longitudinal research and demographic considerations are crucial for inclusive educational strategies. Using diverse methods like mixed-methods and technology can provide deeper insights.